Nivolumab + Ipilimumab as Immunotherapeutic Boost in Metastatic Urothelial Carcinoma: A Nonrandomized Clinical Trial - Grimm, Marc Oliver; Schostak, Martin; Grün, Christine Barbara; Loidl, Wolfgang; Pichler, Martin; Zimmermann, Uwe; Schmitz-Dräger, Bernd; Steiner, Thomas; Roghmann, Florian; Niegisch, Günter; Bolenz, Christian; Schmitz, Marc; et al. (JAMA Oncology, 2024)
Importance: Studies with nivolumab, an approved therapy for metastatic urothelial carcinoma (mUC) after platinum-based chemotherapy, demonstrate improved outcomes with added high-dose ipilimumab. Objective: To assess efficacy and safety of a tailored approach using nivolumab + ipilimumab as an immunotherapeutic boost for mUC. Design, Setting, and Participants: In this phase 2 nonrandomized trial, patients with mUC composed 2 cohorts. Cohort 1 received first-line or second-/third-line nivolumab with escalating doses of ipilimumab, and cohort 2 received second-/third-line nivolumab with high-dose ipilimumab. Recruitment spanned 26 sites in Germany and Austria from August 8, 2017, to February 18, 2021. All patients had a 70% or higher Karnofsky Performance Score and measurable disease per Response Evaluation Criteria in Solid Tumours, version 1.1. Interventions: All patients initiated 4 doses of 240-mg nivolumab (1× every 2 wk). Week 8 nonresponders received nivolumab + ipilimumab (1× every 3 wk). Cohort 1 received 2 doses of 3-mg/kg nivolumab + 1-mg/kg ipilimumab followed by 2 doses of 1-mg/kg nivolumab + 3-mg/kg ipilimumab if no response. Due to safety concerns, cohort 1 treatment was halted, and first-line cohort 2 treatment was not pursued. Cohort 2 received 2 to 4 doses of 1-mg/kg nivolumab + 3-mg/kg ipilimumab. Responders continued with nivolumab maintenance but could receive nivolumab + ipilimumab for later progression. Main Outcomes and Measures: The primary end point was objective response rate. Results: The study comprised 169 patients (118 [69.8%] men; median [range] age, 68 [37-84] years): 86 in cohort 1 (42 first-line; 44 second-/third-line) and 83 in cohort 2. The median (IQR) follow-up times were 10.4 (4.2-23.5) months (first-line cohort 1), 7.5 (3.1-23.8) months (second-/third-line cohort 1), and 6.2 (3.2-22.7) months (cohort 2). Response rates to nivolumab induction were 12/42 (29%, first-line cohort 1), 10/44 (23%, second-/third-line cohort 1), and 17/83 (20%, cohort 2). Response rates to a tailored approach were 20/42 (48% [90% CI, 34%-61%], first-line cohort 1), 12/44 (27% [90% CI, 17%-40%], second-/third-line cohort 1), and 27/83 (33% [90% CI, 23%-42%], cohort 2). Three-year overall survival rates for first-line cohort 1, second-/third-line cohort 1, and cohort 2 using the Kaplan-Meier method were 32% (95% CI, 17%-49%), 19% (95% CI, 8%-33%), and 34% (95% CI, 23%-44%), respectively. Conclusions and Relevance: In this nonrandomized trial, although first-line cohort 1 treatment improved objective response rates, considerable progression events urge caution with this as a first-line therapy. Second-/third-line cohort 1 treatment did not improve response rates compared with nivolumab monotherapy. However, added high-dose ipilimumab may improve tumor response and survival in patients with mUC. Trial Registration: ClinicalTrials.gov Identifier: NCT03219775.
CRIS-Team Scopus Importer:2024-05-24